Relationship between sleep disorders and depressive symptoms among young women in Japan: a web-based cross-sectional study - Yuta Suzuki; Yukio Urabe; Noriaki Maeda; Satoshi Arima; Tsubasa Tashiro; Rami Mizuta; Takeru Abekura; Sakura Oda; Satoshi Onoue (BMJ Open, 2025)
Objectives Japanese people are known to get the least amount of sleep in the world, and in particular, the increase in sleep deprived young women is a serious problem. Sleep deprivation is considered to be associated with depression, but the factors involved in this problem are unclear. This study aimed to examine the association between sociodemographic factors, lifestyle choices, sleep-related characteristics and depressive symptoms in young Japanese women.Design Web-based cross-sectional study.Participants We distributed an online survey aiming to recruit young Japanese women ages 18 to 29 from 8 November 2022 to 2 February 2023.Primary and secondary outcome measures Sociodemographic, lifestyle, health, and sleep characteristics were compared among participants according to the presence or absence of depressive symptoms, as assessed by the Patient Health Questionnaire 2 (Cut-off value: 3 points).Results Overall, 540 participants aged between 19 and 29 years were enrolled in the study. The overall prevalence of depressive symptoms was 15.6%. The group with depressive symptoms had a higher rate of current smoking status at 38.5% (unadjusted OR 3.716, 95% CI 1.624 to 8.502). Multiple logistic analyses revealed that depressive symptoms were associated with increased sleep onset latency (β=0.282; p=0.048; OR, 1.325; 95% CI, 1.003 to 1.752) and daytime dysfunction (β=0.550; p<0.001; OR, 1.733; 95% CI, 1.281 to 2.343) after adjusting for the effects of smoking habits.Conclusions Depressive symptoms were found to be associated with sleep disorders in young Japanese women, and paying attention to sleep onset latency and daytime dysfunction which are one of the strongest related factors to depressive symptoms could be a clue to improving sleep disorders and depressive symptoms.